2016
DOI: 10.1371/journal.pone.0159604
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus DNA Quantification and Gene Expression in Gliomas of Different Grades

Abstract: Gliomas are the most common type of primary brain tumors. The most aggressive type, Glioblastoma multiforme (GBM), is one of the deadliest human diseases, with an average survival at diagnosis of about 1 year. Previous evidence suggests a link between human cytomegalovirus (HCMV) and gliomas. HCMV has been shown to be present in these tumors and several viral proteins can have oncogenic properties in glioma cells. Here we have investigated the presence of HCMV DNA, RNA and proteins in fifty-two gliomas of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 46 publications
2
16
0
1
Order By: Relevance
“…This included patients who were CMV seropositive (53% of patients in the prospective cohort). Our data are consistent with other reports that also did not identify CMV in tissue of patients with these cancers (1016), but they stand in contrast to several studies by other investigators that reported on detection of CMV in the majority of tissues and cells analyzed (1–9). The key question underlying this controversy is how different investigators and laboratories could come to entirely opposite conclusions when studying the same cancer type and virus.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This included patients who were CMV seropositive (53% of patients in the prospective cohort). Our data are consistent with other reports that also did not identify CMV in tissue of patients with these cancers (1016), but they stand in contrast to several studies by other investigators that reported on detection of CMV in the majority of tissues and cells analyzed (1–9). The key question underlying this controversy is how different investigators and laboratories could come to entirely opposite conclusions when studying the same cancer type and virus.…”
Section: Discussionsupporting
confidence: 93%
“…While several groups reported on their ability to detect CMV (1–9), others were unable to replicate these finding, raising questions about the assays used and their sensitivities for CMV detection (1016). The ongoing controversy of CMV detection in gliomas has significant clinical implications since suppression of CMV replication with antiviral therapy could potentially modify the prognosis of these cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Most of this debate stems from the fact that different research groups, often using different assays, have generated evidence to support or refute the presence of HCMV in GBM tumors. There is a large amount of research supporting both sides of this issue (Amirian, Bondy, Mo, Bainbridge, & Scheurer, 2014; Baryawno et al, 2011; Baumgarten et al, 2014; Cosset et al, 2014; Fornara et al, 2016; Hashida et al, 2015; Holdhoff et al, 2015; Joseph, McDermott, Baryshnikova, Cobbs, & Ulasov, 2017; Khoury et al, 2013; Lehrer, Green, Rosenzweig, & Rendo, 2015; Libard et al, 2014; McFaline-Figueroa & Wen, 2017; Prins, Cloughesy, & Liau, 2008; Rahbar et al, 2012; Sardi et al, 2015; Schelhorn et al, 2013; Shamran et al, 2015; Solomon, Ramkissoon, Milner, & Folkerth, 2014; Stangherlin et al, 2016; Strong et al, 2016; Wolmer-Solberg et al, 2013) that we summarize in Fig. 1B–D.…”
Section: Introductionmentioning
confidence: 91%
“…The association of HCMV with gliomas has been a topic greatly debated in the brain tumor field. Increasing evidences demonstrated that HCMV presented in gliomas, especially in GBM, the most malignant type [Stangherlin et al, ]. However, previous studies have not focused on the relationship between HCMV infection and GCSCs.…”
Section: Discussionmentioning
confidence: 99%